Dream Team for Honey Bee Health: Pollen and Unmanipulated Gut Microbiota Promote Worker Longevity and Body Weight - Brown, Andrew F.; Rodriguez, Victor; Brzoska, Camille; Pfister, Judith; Neumann, Peter; Retschnig, Gina (Frontiers in Sustainable Food Systems, 2022)
Gut microbiota are known to foster pollen digestion in honey bee workers, Apis mellifera, thereby enhancing longevity and body weight gain. However, it is currently not known how longevity and body weight gain are effected when gut microbiota are reduced in bees with or without access to pollen. Here, using a hoarding cage set-up with freshly emerged summer workers, we manipulated the gut microbiota of half the bees with the antibiotic tetracycline (ABX), and left the other half untreated on a sucrose solution diet. Afterwards, all bees were assigned to either sucrose diets or sucrose plus ad libitum access to pollen (N = 4 treatments, N = 26 bees/treatment, N = 10 replicates/treatment, N = 1,040 total workers). The data confirm that pollen has a positive effect on longevity and body weight in workers with an unmanipulated gut microbiota. Surprisingly, the antibiotics alone also improved the longevity and body weight of the workers fed a strictly sucrose diet, potentially explained by the reduction of harmful bacteria. However, this positive effect was reversed from an observed antagonistic interaction between pollen and antibiotics, underscoring the innate value of natural microbiota on pollen digestion. In conclusion, a combination of adequate pollen supply and an unmanipulated gut microbiota appears crucial to honey bee worker health, calling for respective efforts to ensure both in managed colonies.